(untitled) (Journal of Dhaka National Medical College & Hospital, 2022)
Objective: To assess the frequently prescribed anti-diabetic medication at initiation of treatment. Methods: A descriptive, cross sectional study was conducted from January 2019 to June 2019 among 300 patients attending at medicine outpatient department of upzilla health complex, Sitakundo, Chittagong after obtaining requisite consent from the patients. Data were collected through the assessment of patients in the Outpatient Department. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the frequently prescribed anti-diabetic medication at initiation of treatment. The study was approved by the institutional ethical committee. Results: In a pool of 300 type 2 diabetes, most patients (57.3%) belonged to the middle age group 41-60 years. Female patients (74.3%) were more than the male patients at the outpatient department. Type 2 DM is more common in urban area (65.7%). Most of the patients were initially treated with metformin (38.3%) followed by sulfonylureas (20.0%) and insulin (10.7%). Conclusion: Most of the patients were initially treated with metformin followed by sulfonylureas and insulin. j. Dhaka National Med. Coll. Hos. 2022; 28 (01): 31-33